Kinerja Dosen Wanita Bidang Kesehatan dalam Konflik Peran Ganda, Stres, dan Motivasi - Wa Ode Ameitha Ladiaz; Arum Dian Pratiwi; Syefira Salsabila (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
Performance is the work achievement of a person, which can be seen from the level of achievement of results or the implementation of certain tasks. The performance of female lecturers can be disrupted due to dual role conflict that causes stress, as well as lack of motivation, where efforts to balance professional and personal responsibilities often reduce focus, productivity, and effectiveness in carrying out academic tasks. This study aims to determine how dual role conflict, work stress, and work motivation relate to the performance of female lecturers at the Faculty of Public Health, Pharmacy, and Medicine, Halu Oleo University in 2024. The type of research is quantitative with a cross-sectional study design and observational analytic method. All female lecturers at the Faculty of Medicine, Pharmacy, and Public Health, Halu Oleo University became the population. The sample in the study amounted to 74 female lecturers selected using the Simple Random Sampling (SRS) method. Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed that dual role conflict (p=0.019) and work motivation (p=0.016) were related to performance, while work stress (p=0.275) was not related.